Design Flood Discharge of 50 Years in Garang River Using Nakasayu Synthetic Unit Hydrograph Method - Maulana, Nadya Kintantrie; Sutopo, Yeri (Semarang State University, 2020)
Abstract: Various kinds of buildings in civil engineering require careful planning. For example, in the planning of a water building needed a method to calculate the design flood discharge before starting to plan the dimensions of the building to meet the effectiveness of the water structure. Design flood discharge can be determined using several hydrograph methods that have been used in water building planning in Indonesia. One of the popular hydrograph method used is the Nakayasu Synthetic Unit Hydrograph method. In this case, the design flood discharge is located in the Garang watershed, precisely in Semarang City, province of Central Java, using rainfall data for the past 16 years. Hydrological analysis is carried out first before determining the design flood discharge with a return period of 2, 5, 10, 25, and 50 years. The results of the design flood discharge using Nakayasu method respectively were 305,522 m3/s, 390,742 m3/s, 447,783 m3/s, 520,560 m3/s, and 574,912 m3/s.